16. KNOWLEDGE AND PRACTICE OF ANTIBIOTICS USE AND SOME RELATED FACTORS AMONG PEOPLE IN MINH LANG COMMUNE, VU THU DISTRICT, THAI BINH PROVINCE IN 2023 (Tạp chí Y học Cộng đồng, 2024)
Objectives: To describe the knowledge and practice of people on antibiotics use and analyze some related factors to knowledge and practice of people on antibiotics use in Minh Lang commune, Vu Thu district, Thai Binh province in 2023Methodology: The study employed a cross-sectional study design with the study sample size of 366 people.Results: Results indicated moderate knowledge prevalence (48.9%) and predominantly high-level antibiotic usage practices (67.5%). Factors influencing knowledge and practices included familial ties to healthcare, exposure to health education campaigns, and proximity to healthcare facilities. Targeted educational interventions are crucial for enhancing understanding and promoting responsible antibiotic usage practices, particularly in rural communities vulnerable to antibiotic resistance.
Keywords: antibiotics; antibiotics resistance; antibiotic use; KAP; related factors